Pakistan : Report on the Observance of Standards and Codes (ROSC) : Corporate Governance Country Assessment - World Bank (Washington, DC, 2012)
This report provides an assessment of Pakistan's corporate governance policy framework. In Pakistan, awareness of the importance of good corporate governance is high among policymakers and standard setters. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Pakistan. The focus of the assessment is on listed companies, although reference is also made to banks and other financial institutions. Reform to improve corporate governance has been significant, including the introduction of a code of corporate governance and increased vigilance by regulators. Highly concentrated control by significant shareholders has limited the objectivity of boards and reduced the impact of some of the recent reforms. More generally, many smaller and family-owned companies have a limited awareness of the potential benefits of improved corporate governance. Corporate governance reform needs to percolate throughout the corporate sector, including family-owned businesses. The report concludes that further steps need to be taken to protect shareholder rights, including disclosure of beneficial ownership, and that boards must become more effective, with stronger fiduciary duties, and more capable independent directors.